TRANSHUMANISM AND THE IMPLICATIONS OF INTELLECTUAL AND TECHNOLOGY IN THE BODY ART - Dr. Nada Aaied Yousif (European Journal of Humanities and Educational Advancements, 2022)
The body has entered a new stage in the digital world to reveal an age associated with intellectual and technical transformations according to the controversies and debates that led to the birth of the post human age trans humanism, which promises to increase the capabilities of the body as physical as well as open the way to intellectual transformations that hit the dogmatic limits of the self and the sacred body To review the features of the digital age in order to communicate the cosmic and bring about vibrations in the aesthetic awareness and move to the era of circulation to devise mechanisms and concepts that reflect the society and belong to it all the variables. As a result of the study of the mutual effects between art and science to research in the transitions of methods of body art, this study was entitled "Trans humanism and the implications of intellectual and technology in the body art ". This paper contains concept of post-human, and discusses technological implications of the body art and undergone transformations resulting from those stylistic implications. The third chapter deals with analyzing the samples. Finally Under the last title “results and discussion”, the findings of the study are summarized.